Kinetics and Mechanism of SDS Catalyzed Reaction between Ethanol and N-bromobenzamide. - PARE, BRIJESH; CHOUBE , AJIT; BHAGWAT, V.W.; RADHAKRISHNAN, ASHA (Asian Journal of Chemistry, 2010)
A reaction between ethanol and N-bromobenzamide (NBB) in acidic medium has been found to be catalyzed by an anionic surfactant SDS. The log (a -x) vs. t curve displays an inflection. i.e., slow first stage followed by relatively faster second stage. In both the stages the reaction follows first order behaviour with respect to substrate and N-bromobenzamide. The cause of autocatalysis has been attributed to Br - ions, which was further substantiated by the removal of first stage on initial addition of potassium bromide. The pre-micellar kinetics has been rationalised in the light of pseudophase model. The positive cooperativity index has been computed (n = 1.47). The solvent composition variation and addition of benzamide have also been studied. On the basis of the various observations and product characterization, most plausible mechanisms . have been envisaged.